Atopic dermatitis: new evidence on the role of allergic inflammation. Issue 5 (October 2016) - Heratizadeh, Annice
Abstract : Purpose of review: Atopic dermatitis is a chronic relapsing inflammatory skin disease. In the presence of a complex genetic background, there is increasing evidence for the role of specific allergenic trigger factors in perpetuating skin inflammation in sensitized atopic dermatitis patients. In this review, clinical and in-vitro data so far published on allergen-induced adaptive immune responses in atopic dermatitis are summarized. Recent findings: Emerging new data have been published particularly on adaptive immune responses to inhalant allergens in atopic dermatitis. In a randomized controlled study, the induction of a flare-up by grass pollen exposure in sensitized atopic dermatitis patients could be demonstrated for the first time. T cells directed to the two major allergens of house dust mite have been characterized to display a Th2, and moreover, a Th17 and Th2/Th17 phenotype in sensitized atopic dermatitis patients. With regard to microbial antigens, T cell-mediated immune responses directed to proteins of the species themselves can be observed – as has been published for Staphylococcus aureus and Malassezia spp. Beyond this, specific T-cell activation to cross-reacting human proteins might further trigger the disease in distinct patients. The role of 'autoallergic' phenomena in atopic dermatitis, because of human antigens without known cross-reactivity to environmental allergens, is currently under investigation as well. Summary: Recent findings on immunological and clinical characteristics of adaptive immune responses to allergens in atopic dermatitis, but also on the identification of new, potentially relevant allergen sources might contribute to the development of effective treatment strategies 'customized' for allergic inflammation in atopic dermatitis in future.